The relationship between servicescape, experiential values, self-image congruity and loyalty intention of customers towards department stores in Malaysia / Zuraini Alias - Alias, Zuraini (Institute of Graduate Studies, UiTM, 2017)
The changing lifestyles of consumers are altering the way they shop and the kinds of experiences they seek when shopping. In particular, the increasing significance of e-commerce and the advancement of internet technology have a direct and fast impact in the multiplicity of goods offerings, designs of the websites, services, and various aspects of information. Despite the advancement of technology that has induced a large majority of consumers to shop online, there are still those who prefer the experience of shopping at the store where they can see, feel, and touch the goods they are buying and experience the environment when shopping. It is on this premise that this study is envisaged to determine whether environmental cues brought about by servicescape developments of department stores in Malaysia do induce loyalty intention among the shoppers. Using experiential values and self-image congruity as the mediating variables, this study addresses the extent that loyalty intention of shoppers to department stores in Malaysia are influenced by servicescape dimensions in getting them to re-patronize or to shop again at specific department stores, thus inferring loyalty intention. Although a few previous studies have addressed the linkage between servicescape and loyalty intention, none has actually integrated experiential values and self-image congruity as mediating variables in the relationship.